Substituting seaweed with corn leaf in diet of sea cucumber (Apostichopus japonicus): effects on growth, feed conversion ratio and feed digestibility - Wu, B.; Xia, S.; Rahman, Mohammad Mustafizur; Rajkumar, M.; Fu, Z.; Tan, J.; Yang, A. (Elsevier B.V., 2015)
A 60-day experiment was conducted to develop a practical diet for sea cucumber (Apostichopus japonicus) substituting seaweed with corn leaf. Five experimental diets were constructed with each containing a 70% sea mud. The other 30% is composed of (A) 30% Sargassum thunbergii (seaweed) only, (B) 22.5% seaweed and 7.5% corn (Zea mays) leaves, (C) 15% seaweed and 15% corn leaves, (D) 7.5% seaweed and 22.5% corn leaves and (E) 30% corn leaves only. The experiment was conducted in 15 plastic aquaria containing seawater, each of which stocked with 20 sea cucumbers. Three replicate groups of sea cucumber were fed one of the five experimental diets. The results revealed that the apparent digestibility coefficients for dry matter (ADMD) and crude protein (ACPD) of the test diets decreased with increasing corn leaf content in diets. Corn leaf content in the sea cucumber diet did not affect the body composition of sea cucumber. 22.5% seaweed can be replaced with powdered corn leaf in the sea cucumber diet without any negative effects on weight gain and specific growth rate (SGR) of sea cucumber. Diet containing higher than 15% corn leaf significantly increased the feed conversion ratio (FCR) of sea cucumber. However, the growth performance and FCR of sea cucumber fed the mixed diet of 15% corn leaf plus 15% seaweedwere better than the growth performance and FCR of sea cucumber fed other experimental diets. The regression analysis of dietary corn leaf inclusion level versus SGR revealed that the optimal corn leaf inclusion level was 11.2% for the best growth rate of sea cucumber. Therefore, under the present experimental design and condition, a diet with 70% sea mud plus 18.8% seaweed plus 11.2% corn leaf can be recommended for the best growth performance of sea cucumber. The findings of this study will encourage feed manufacturers and sea cucumber culturists to utilize corn leaf in producing low-cost aqua-feed.